Case report: Microcirculatory leukocytes in a pediatric patient with severe SARS-CoV-2 pneumonia. Findings of leukocytes trafficking beyond the lungs - Bottari, Gabriella; Ince, Can; Confalone, Valerio; Perdichizzi, Salvatore; Casamento Tumeo, Chiara; Nunziata, Joseph; Bernardi, Stefania; Calò Carducci, Francesca; Lancella, Laura; Bernaschi, Paola; Russo, Cristina; Perno, Carlo Federico; et al. (Frontiers in Pediatrics, 2022)
Background: SARS-CoV2 can lead to excessive coagulation and thrombo-inflammation with deposition of microthrombi and microvascular dysfunction. Several studies in human and animal models have already evidenced biomarkers of endothelial injury during Sars-Cov-2 infection. Real-time observation of sublingual microcirculation using an handheld vital microscopy with a Incident Dark Field technique could represent a non-invasive way to assess early signs of microvascular dysfunction and endothelial inflammation in patients with severe COVID-19 infection. Clinical case: We report for the first time in a pediatric patient with severe Sars-CoV-2 pneumonia findings about microcirculatory leukocytes in the sublingual microcirculation of a 7 month-old patient admitted to our PICU using handheld vital microscopy with Incident Dark Field technique. Results: Sublingual microcirculation analysis revealed the presence of microcirculatory alterations and an extensive presence of leukocytes in the patient’s sublingual microcirculation. It’s significant to underline how the patient didn’t show a contextual significant increase in inflammatory biomarkers or other clinical signs related to an inflammatory response, beyond the presence of severe hypoxic respiratory failure. Conclusions: Leukocyte activation in multiple organs can occur at the endothelial lining of the microvasculature where a surge of pro-inflammatory mediators can result in accumulation of activated leukocytes and degradation of the endothelium. The introduction of a method to assess in a non-invasive, real-time manner the extent of inflammation in a patient with COVID19 could lead to potential clinical and therapeutic implications. However, more studies are required to prove that studying leukocytes microcirculation using sublingual microcirculation analysis could be useful as a bedside point of care monitor to predict the presence of systemic inflammation associated with the impact of COVID-19, leading in a late phase of severe Sars-CoV-2 infection to a microvascular dysfunction and micro-thrombosis.